Modeling and Implementation of an Adaptive Wireless Sensor Network for Low Power IoT Applications - Olcay, K.; Taparci, E.; Akmandor, M.O.; Kabakulak, B.; Sarioglu, B.; Gokdel, Y.D. (Institute of Electrical and Electronics Engineers Inc., 2023)
Wireless Sensor Networks (WSNs) consist of low cost and energy small electronic devices such as sensors, actuators, routers and gateways. A WSN can sense various type of data, such as temperature, humidity, pH.. etc, with the sensors scattered on an agricultural region and collect the data at a cloud database via multi-hop data transmission routes. The number of periods that a WSN operates is the network lifetime which strongly depends on the limited battery energy of the devices. Hence, in order to prolong the lifetime, we propose a centralized mathematical model which deploys minimum number of devices within limited budget, efficiently utilizes the device battery by planning their active/sleep schedules and determining the minimum energy consuming data flow paths towards the cloud. We also realized the proposed model on hardware level using low power embedded system architectures. © 2023 University of Split, FESB.
8th International Conference on Smart and Sustainable Technologies, SpliTech 2023 -- 20 June 2023 through 23 June 2023 -- Hybrid, Split/Bol -- 191291
Keywords: Energy Efficiency; Internet Of Things; Mathematical Programming; Narrow-Band Communication; Optimization; Sensor Networks; Budget Control; Data Transfer; Electric Batteries; Gateways (Computer Networks); Internet Of Things; Low Power Electronics; Mathematical Programming; Wireless Sensor Networks; Cloud Database; Electronics Devices; Low Power; Low-Costs; Lower Energies; Narrow Band Communications; Optimisations; Sensor/Actuator; Sensors Network; Temperature/ Humidities; Energy Efficiency